RELATIONSHIP BETWEEN ABDOMINAL GYMNASTIC COUNSELING AND ADOLESCENT GIRLS' KNOWLEDGE ABOUT XI HANDLINGOFDYSMENORRHHEA IN SMAN 3 PALU - Pani, Widya; Kaparang, Mercy Joice (STIKes Kapuas Raya, 2019)
The earliest changes in female adolescence are menstruation which can cause dysmenorrhea problems. The incidence of dysmenorhhea in Indonesia is quite high 64,24%, research by Marlinda, et al (2012) from 15 respondents there are 33,3% suffer dysmenorhhea which cause effect of adolescent unable to learn, unable to concentrate, cry, not even go to school. The purpose of this study is to know the relationship of abdominal gymnastics counseling with increasing knowledge of young women about handling dysmenorhhea in class XI in SMA Negeri 3 Palu.The type of research used is pre experiment design with one group pretest and posttest design. Population and sample in this research is adolescent daughter of class XI counted 268 people. The sample in this study was taken using slovin formula with the proportion of 15% with the result of 38 added 10% to prevent missing data of the person to 42 by sampling technique simple random sampling.The result showed that from 42 respondents 32 respondents (84.2%) had less knowledge, after given intervention given posttest 1 got 4 respondents (7,9%) knowledgeable less, while 1 week after intervention given posttest 2 not got respondent with knowledge less. Analysis using friedman test and then followed by post hoc analysis using wilcoxon test obtained p value 0,000 (p <0,005).The Conclusion There is a relationship of abdominal gymnastics counseling with the knowledge of young women about handling dysmenorhhea in class XI in SMAN 3 hammer. It is expected that the school actively provides periodic information on repoduksi especially dysmenorhhea in cooperation with PIKRR and UKS